2018
DOI: 10.1038/s41598-018-19961-3
|View full text |Cite
|
Sign up to set email alerts
|

Critical aggregation concentration for the formation of early Amyloid-β (1–42) oligomers

Abstract: The oligomers formed during the early steps of amyloid aggregation are thought to be responsible for the neurotoxic damage associated with Alzheimer's disease. It is therefore of great interest to characterize this early aggregation process and the aggregates formed, especially for the most significant peptide in amyloid fibrils, Amyloid-β(1-42) (Aβ42). For this purpose, we directly monitored the changes in size and concentration of initially monomeric Aβ42 samples, using Fluorescence Correlation Spectroscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 42 publications
(54 reference statements)
5
124
1
Order By: Relevance
“…It should be mentioned that both AUC and MST report the information about the bound and unbound states of the labeled molecule. At a concentration lower than the critical aggregation concentration of about 90 nM, Aβ is unlikely to form aggregates within the time scale of both experiments, which definitely helps to reduce the incidence of multiple binding between Aβ oligomers and antibodies. The size distribution of all antibody‐containing FITC‐Aβ42 samples also revealed that complexes with only one antibody molecule were the dominant species in solution.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that both AUC and MST report the information about the bound and unbound states of the labeled molecule. At a concentration lower than the critical aggregation concentration of about 90 nM, Aβ is unlikely to form aggregates within the time scale of both experiments, which definitely helps to reduce the incidence of multiple binding between Aβ oligomers and antibodies. The size distribution of all antibody‐containing FITC‐Aβ42 samples also revealed that complexes with only one antibody molecule were the dominant species in solution.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46][47][48][49] The amphiphilicity of Aβ is itself a cause of its self-association. Several authors have noted the micelle-like nature of some Aβ soluble oligomers, [50][51][52][53][54] and in fibrils, the parallel, in-register nature of the β-sheets tends to minimize the exposure of the hydrophobic domains to the aqueous medium. In addition, it has been shown that a short internal fragment of Aβ, Aβ16-21, forms antiparallel β-sheets when the N-terminus is acetylated, but the orientation flips to parallel and in-register when the N-terminus is octanoylated-a change that also renders the peptide more amphiphilic in monolayers at the air-water interface.…”
Section: Effects Of Lipid Surfaces and Other Amphiphilic Or Hydrophmentioning
confidence: 99%
“…At time zero, unstructured protein globules of various sizes were identified (Figure 2a). The smallest structures have a diameter of ~3.6 nm, which correlates well to the size of Aβ monomer (hydrodynamic radius of 1.8 nm) [71]. Larger globular structures are 6 – 50 nm in diameter and lack any fibrillar structures.…”
Section: Resultsmentioning
confidence: 99%